Relationship between Smokeless Tobacco Dependence and Psychiatric Disorders (Academia Journal of Medicine, 2019)
Background: The epidemiology of nicotine dependence indicates how strongly addictive a drug it is that nearly half of those who ever smoked  steadily for a month become highly nicotine dependent. It is a psychoactive substance that induces euphoria, reinforces its own use, and leads  to nicotine withdrawal syndrome when it is absent. Subjects and Methods: Written informed consent was taken from all the cases and  controls prior to the detailed assessment. The personal data was recorded in the socio demographic data. They were administrated Modified  Fagerstrom test for nicotine dependence [FTND] and those who were nicotine dependent were then screened for psychiatric morbidity using  GHQ – 12 [69] screening questionnaire. Results: Among those with psychiatric diagnosis majority had Major Depressive Disorder [24%],  Generalized Anxiety disorder [18%], Mixed Anxiety Depressive disorder [10%] and Alcohol dependence syndrome[14%] as compared to non nicotine dependents. Conclusion: Severity of Anxiety and depression increased with the severity of nicotine dependence among the  cases.Coping skills were not significantly different between cases and controls.
Keywords: Smokeless tobacco dependence; Psychiatric disorders; Modified Fagerstrom test for nicotine dependence